Ultrasonographic assessment of optic nerve sheath diameter on the affected and unaffected sides as a predictor of clinical deterioration at discharge in patients with large hemispheric infarction - Li, Changlan; Li, Yanping; Gu, Xunhu; Zhang, Yancai; Cheng, Xiaoqian; Wang, Wei (Frontiers in Neurology, 2025)
Background and objectivesProgressive cerebral edema worsens prognosis in large hemispheric infarction (LHI). Ultrasonographic optic nerve sheath diameter (ONSD) measurement provides a non-invasive method for estimating intracranial pressure. This study aimed to evaluate the predictive value of affected- and unaffected-side ONSD for clinical deterioration at discharge in LHI patients and to provide reference data on factors linked to deterioration, follow-up outcomes, and longitudinal ONSD monitoring.MethodsThis retrospective study enrolled 35 LHI patients, classified into two groups: improved and deteriorated, based on clinical and imaging findings at discharge. Demographic and clinical characteristics were compared. Receiver operating characteristic (ROC) analysis evaluated the predictive performance of affected- and unaffected-side ONSD. Area under the curve (AUC) difference was compared using the DeLong test. Post-discharge follow-up at 30 and 90 days was conducted via telephone interviews. Longitudinal changes in affected- and unaffected-side ONSD were depicted using line graphs for patients with extended stays in the neuro-intensive care unit (NICU).ResultsStatistically significant variables included age (p = 0.002), female (p = 0.002), history of atrial fibrillation (p = 0.044), GCS score (p = 0.028), affected-side ONSD (p = 0.002), unaffected-side ONSD (p = 0.012), and duration of NICU stay (p = 0.002). A positive linear correlation was identified between ONSD values and discharge outcomes. The optimal cut-off for predicting deterioration was 5.54 mm for affected-side ONSD (sensitivity 81.3%, specificity 78.9%, AUC = 0.814) versus 5.57 mm for the unaffected-side (68.8, 78.9%, AUC = 0.757), with no significant AUC difference between sides. The overall 30-day post-discharge mortality was 39.29%. Longitudinal changes in bilateral ONSD showed remarkable overlap in both individual and group observations. Patients with improved outcomes exhibited decreasing ONSD trends, whereas those with deterioration displayed increasing trends.ConclusionPreoperative ONSD measurement is a feasible and practical predictor of discharge prognosis in LHI patients, with both affected and unaffected sides providing reliable monitoring. Factors including age, female, history of atrial fibrillation, GCS score, ONSD on either side, and NICU stay duration may influence outcomes. The high short-term mortality underscores the importance of the post-discharge transition management. The clinical value of longitudinal ONSD monitoring requires further investigation.